ERPs Studies of Short- and Long-Term Habituation in Humans: A Systematic Review - Pinto, Jorge; Vogel, Edgar; Aylwin, María de la Luz; Kreither, Johanna (Psykhe, 2022)
Habituation is a type of learning that consists of a decrease in the response to a repetitive stimulus. The traditional view is that habituation comprises two processes: a transitory one called short-term habituation (STH), promoted by stimulus presentations at short intervals, and a more durable one called long-term habituation (LTH), promoted by more spaced repetitions. Due to the importance of time in this distinction and in an attempt to elucidate its underlying mechanisms, several studies have sought to relate habituation to brain activity through the analysis of event-related potentials (ERPs). We performed a systematic review of studies on habituation of ERPs in humans using the PRISMA methodology. A total of 175 articles were evaluated for eligibility and 145 were included. Most of the studies focused on short-term effects, demonstrating habituation in a range of ERP components such as P50, P1, N1, P2, N2, and P3. These studies revealed that STH occurs with intervals ranging from 75 ms to 4 s with an optimal of 500 ms, but it does not with intervals greater than 10 s. There are also some studies showing that the P1, N1, P2, N2, and P3 components exhibit LTH with inter-stimulus intervals between 3 and 10 seconds, but the evidence is yet insufficient to establish a secure conclusion with respect to LTH. We propose that future studies should use a wider range of inter-stimulus intervals with tests of both short-and long-term habituation so that the specific neurophysiological components of each type of habituation could be determined.